Big Five Trails: A Critical Review - Najm Abood Najm (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
This study seeks to provide a broad and thorough review of the literature on the big five traits (BFT) and its major developments through a long history of conceptual and applied studies in many areas that have been conducted on large samples of individuals, groups and countries. The BFT is the most widely accepted and most prominent model to describe the structure of personality traits, so this study sought to identify them in order to achieve a better understanding as well as for consideration by researchers in their future studies. This review focused on the eight key observations related to the BFT. These observations are as follows: meaning of the traits; the history of the BFT model; unity or hierarchy of traits; number of the traits; three perspectives on BFT; BFT questionnaires; BFT and performance; and the need for a sixth trait. The results of the study clearly confirmed that there are problems with universal models that tend to generalize a limited number of dimensions in order to interpret personality across borders and cultures. This generalization of the models is accompanied by the numerous observations and problems mentioned in the above eight points.